Violence and Motherhood: A Case Study about the Personality Profile and Attachment Style of a Filicide Woman. Issue 5 (3rd May 2020) - Giacchetti, Nicoletta; Pancheri, Corinna; Williams, Riccardo; Marconi, Michela; Magistro, Rosa; Pozzuoli, Luciano; Aceti, Franca
ABSTRACT: Several studies focused on mothers' psychopathological and environmental risk factors linked to filicide, but few studies explored personality characteristics of these women. Considering that the transition to motherhood requires the activation of deep personality resources, aim of this report is to describe the personality profile and attachment style of a woman who killed her 5-year-old son and tried to kill her 3-months-old daughter. The woman was assessed using Structured Clinical Interview for DSM-IV Axis I (SCID-I), Graphical Tests, Big Five Inventory (BFI), Temperament and Character Inventory (TCI), Adult Attachment Interview (AAI) and Minnesota Multiphasic Personality Inventory-2 (MMPI-2). Test results showed a profile characterized by emotional instability, inner fragility and tendency to experience negative emotions, with the possibility of apparently unmotivated hostile behaviors and a tendency towards complacency. AAI results showed a distancing attachment style shading light into the importance of the internalized maternal figure. Examining the mother's mental state, with attention on personality traits and attachment style, could help clinicians to detect specific temperament patterns that may carry out violent behaviours.